Fault Tolerant Discrete Control Technique for PV Fed Stepper Motor Drive - et. al., Viji K , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper deals with the fault tolerant discrete control technique for the Photo Voltaic (PV) fed 3-phase stepper motor (SM). The operation of stepper motor is complex under high speed applications due to dificulty in locating the step-angle and there is a chance of missing the step-angle. A robust discrete sliding mode control (DSMC) algorithm is developed to overcome this problem along with the fault tolerant topology. The drive is powered by PV array and using perturb and observe (P&O) algorithm maximum power is retrieved from the source. The closed loop control of this drive is implemented using MATLAB/SIMULINK simulation software and the speed control of stepper motor is achieved by introducing stepped reference signal. The fault tolerance is verified by introducing open circuit (OC) and short circuit (SC) faults in the driver circuit and the speed response of the same is plotted. The robustness of the discrete controller is proved by introducing changes in the irradiance of PV array, changes in reference speed and faults in the driver circuit. The oveall system is cheap, compact, robust and reliable under all test conditions and suitable for very low and very high speed applications.